Penggunaan Media Kartu Huruf untuk Meningkatkan Kemampuan Baca Tulis Al-Quran pada Siswa Tunagrahita Kelas II di SDLB Negeri Sumberjo Kandat - Hidayati, Ririn (Didaktika Religia, 2015)
The study investigates the use of letter cards to help children with special needs (mental retardation) in learning to read and write Koran. This is action research with three cycles. Each cycle is intended to make students active and creative. Education is for all citizens, including children with special needs (mental retardation. The difficulties of children with special needs (mental retardation) in learning to read and write the Koran is because they do not have the ability to read and write like normal children in general. Therefore, teachers should be skillful at picking strategies, methods and media appropriate to apply to children with special needs, in this case the teachers use letter cards in increasing the literacy of the Koran. This is intended to facilitate the children to read and write the Koran. Students are trained to understand their own ability to establish independence, so that their action is more effective and enjoyable so that optimal learning results.